Central composite rotational design (DCCR) for sensory evaluation of dairy desserts - Leal, Ketolly Natanne da Silva; Bastos, Izabella Carneiro; Barros, Sara Regina Ribeiro Carneiro de (Brazilian Journal of Science, 2022)
To investigate consumer acceptance of the product, a sensory analysis is recommended. The objective of the sensorial analysis is to map the levels of acceptance, profile and characteristics of the consumers. The characteristics that influence the sensorial quality are: flavor, texture and appearance, therefore, they need to be monitored by means of studies that allow the evaluation of the consumer's eating behavior. There are different sensory evaluation methodologies that can be used, such as: discriminative methods, subjective methods and descriptive methods. However, these classic methodologies have limitations, such as the high cost of maintaining a well-trained sensory team and the amount of sampling. Thus, methodological proposals to solve these limitations have been developed and one of them is based on statistical analysis. Based on this, the present study aimed to apply a factorial experimental design (DCCR) as data analysis for the sensory study, in which the product tested is a white chocolate flavored dairy dessert. Acidity and pH analyzes were performed to correlate with the DCCR results. After processing the data, it was found that among the variables investigated in the sensory analysis, the age of the tasters was the factor that significantly influenced the consumer's intention. The acidity of the product was not altered during the analysis time between 0-60 days, however it presented pH variation, both did not indicate a relationship with the DCCR result.